Metabolic Changes in Cancer Patients - Madeddu, Clelia; Maccio, Antonio; Mantovani, Giovanni (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2011)
In advanced cancer patients, energy metabolism is severely compromised by the occurrence, during the disease progression, of symptoms such as anorexia, nausea and vomiting, which do not allow for a normal nutrition and so a regular supply of carbohydrates, proteins, amino acids and vitamins. In addition to the reduced food intake, important changes of energy metabolism and biochemical/metabolic abnormalities in carbohydrate, protein and lipid biochemistry and metabolism have been observed. The most important carbohydrate abnormalities observed in cachectic cancer patients are increased glucose synthesis, gluconeogenesis and Cory cycle activity, insulin resistance, and decreased glucose tolerance. Protein metabolism changes seem to depend mainly from the lack of body adjustment to the increased energy demands and the inadequate food intake, which determines the activation of glucogenesis starting in particular from protein substrates. From a clinical point of view this metabolic condition is characterized by skeletal muscle atrophy and hypoalbuminemia. Moreover, hypertrigliceridemia, increase of free fatty acids, depletion of fat stores and decrease of LPL concentrations and activity, which is closely related with weight loss, have been constantly observed in advanced cancer patients. It has been suggested that the chronic action of mediators released by tumour cells and immune cells counteracting tumour is the main cause of the metabolic abnormalities characterising the cachectic neoplastic patient. In particular, proinflammatory cytokines IL-1, TNF-α and IL-6 play a central role in the pathogenesis of metabolic derangements associated with cancer-related cachexia. It may be hypothesised that, during the initial phases of neoplastic disease, the synthesis of proinflammatory cytokines leads to an efficient antineoplastic effect. However, their chronic activity leads to severe alterations of cell metabolism, with deleterious effects on body composition, nutritional status and immune system efficiency.
Keywords: leptin